Knowledge on risk factors and warning signs of stroke in Udupi - Maryl Candida Cutinho; Jyothi Chakrabarty; Girish Menon (Wolters Kluwer Medknow Publications, 2022)
Background: World Health Organization reports that stroke is the third among the top 10 causes of death in India. Despite this, knowledge among general public about stroke and its risk factors is a bare minimum. The objective of this study was to assess the knowledge on risk factors and warning signs of stroke among selected caregivers and students. Materials and Methods: A descriptive survey was conducted in the medical, neurologic and cardiac outpatient departments of a tertiary care hospital. The participants of the survey were students of the allied health sciences, nursing and engineering, and care givers of patients attending the outpatient departments. The data on the knowledge of risk factors and warning signs of stroke were collected using convenient sampling technique. Results: Twenty-five percentage of the students and 65% of the care givers had only less than average knowledge on warning signs and risk factors of stroke. Conclusions: Knowledge level of the students as well as the care givers is not satisfactory considering the increasing incidence and mortality related to stroke in India. Therefore, training the individuals on identification of signs of stroke and immediate management is vital.